Analysis of the Effectiveness of High-Intensity Interval Training Methods in Improving Basketball Players Fitness - Hita, I Putu Agus Dharma; Pambayu, Septadi Hanif (Eastasouth Institute, 2024)
This research aims to analyze the effectiveness of High-Intensity Interval Training (HIIT) in improving the fitness of basketball players. Employing a literature review methodology, this study explores recent findings related to the application of HIIT in the context of basketball sports. The literature analysis involves searching and screening various scientific articles covering aspects such as improved cardiorespiratory fitness, muscle strength, time efficiency, and safety considerations. The results indicate that HIIT holds significant potential in enhancing the cardiorespiratory fitness of basketball players, with positive effects on aerobic capacity and cardiorespiratory endurance. Furthermore, HIIT has also shown a positive impact on increasing muscle strength and endurance. The effectiveness of HIIT can be observed in its time efficiency, as this high-intensity training program can deliver significant results in a shorter time compared to conventional training methods. However, the study also highlights the importance of considering the risks and safety considerations in implementing HIIT, emphasizing the need for an individualized approach and careful monitoring. Thus, this research provides a solid foundation for the development of more focused and effective training programs to enhance the performance of basketball players. The practical implications of these findings can assist coaches and fitness professionals in designing exercise programs tailored to the specific needs of basketball players, taking into account cardiorespiratory aspects, muscle strength, time efficiency, and safety.